Relation of Achievement Motivation and Learning Motivation with Learning Outcomes of Physics Students in Universitas Flores - Ilyas Ilyas; an Nisaa Al Mu’min Liu (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2018)
This research was survey, which was correlational aimed at to know the where abouts of asignificant relation between achievement motivation and learning motivation with the learning outcomes ofProgram Studi Pendidikan Fisika Universitas Flores. The population in this study were all students offourth semester Program Studi Pendidikan Fisika Universits Flores, amounting to 64 students. While thesample of 51 students were taken by using the nomogram Hary King. The result of the descriptive analysisshow that (1) achievement motivation the fourth semester students of Program Studi Pendidikan FisikaUniversitas Flores be in medium category (2) the motivation to study physics student the fourth semesterProgram Studi Pendidikan Fisika Universitas Flores be in medium category (3) of the learn physicsstudents the fourth semester of Program Studi Pendidikan Fisika Universitas Flores obtained through atest study results cognitive be in medium category. While the result of the inferential analysis show thatthere is a significant relation between achievement motivation and learning motivation with physicslearning outcomes the foutrh semester of Program Studi Pendidikan Fisika Universitas Flores.